PRODUKSI DAN KEUNTUNGAN HASIL TANAMAN CABAI (Capsicum Sp) DI DESA PULANTAN KECAMATAN AWAYAN KABUPATEN BALANGAN PROVINSI KALIMANTAN SELATAN - Bahrun Bahrun; Rohansyah Rohansyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
The purpose of this study is technically to determine the implementation of the cultivation of cayenne pepper, economically to find out the amount of costs, revenue, income and profits on the cultivation of cayenne pepper in the Village of Pulantan Awayan District.. Average production of 241.70 kg / farmer. Average revenue of Rp.12,085,000.00 / farmer, Average Total Cost of Rp. 6,489,268.35 / farmer Average income of Rp.8,105,795.83 / farmer. average profit of Rp. 5,595,731.65 / farmer. The study was conducted in Pulantan Village, Awayan District, Balangan Regency South Kalimantan Province. Data obtained and processed in this study include primary data and secondary data. The research used the puposive method by intentionally taking farmers who specifically planted cayenne peppers. Whereas the sampling technique is done by census (complete enumeration of all elements of the population. The total number of samples taken is 20 farmers. The data collected is processed in tabulation and then analyzed which includes the costs, revenues, income and profits of the farming of Rawit Chili. Average production of 241.70 kg / farmer. Average income of Rp.12,085,000.00 / farmer, Average Total Cost of Rp. 6,489,268.35 / farmer Average income of Rp8,105,795.83 / farmer. average profit of Rp. 5,595,731.65 / farmer